Cluster 2 of the Temple Complex - Temples of India Project Team (Jio Institute, 2024)
The second cluster of the temple complex includes the Ghateshwar Temple, Mahishasuramardini Temple, Vamana Temple, and Sadashiva Temple. Additionally, a detached torana (ornamental gateway) and doorframe are found within the complex. The complex also houses multiple Shiva lingas arranged in rows and a kund (water tank).